The Influence Of Character: Does Personality Impact Coaching Success? - Lorna J. Stewart; Stephen Palmer; Helen Wilkin; Maire Kerrin (International Journal of Evidence Based Coaching and Mentoring, 2008)
Using the Five Factor Model of personality and the construct general self efficacy this study explores the relationship between coaching clients’ personality and a self-report measure of the transfer of learning from coaching to the workplace. Positive correlations are found between the application of coaching development and conscientiousness, openness to experience, emotional stability and general self-efficacy. Conscientiousness is also found to be associated with generalisation and maintenance of outcomes. Personality measures may have value as a means for identifying coaching clients who require support in order to make manifest the changes experienced in coaching.